2002
DOI: 10.1037/0278-6133.21.6.610
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of perceived self-efficacy to quality of life in chronic obstructive pulmonary disease.

Abstract: From a biomedical perspective, variations in the quality of life of chronic obstructive pulmonary disease (COPD) patients may be attributed to changes in pulmonary function; thus, an increase in lung function should be correlated with an increased score on a health-related quality-of-life measure. However, inconsistent results regarding correlations between various measures of pulmonary function and quality of life have been reported in the literature. The authors evaluated a social cognitive model of quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 15 publications
1
34
0
8
Order By: Relevance
“…Consequently, the results of this study, showing a significant improvement in self-efficacy during rehabilitation, are rather remarkable. Only a few other studies have assessed perceptions of personal control in patients with COPD [15,[52][53][54][55] and, therefore, this study contributes to the existing literature.…”
Section: Personal Controlmentioning
confidence: 89%
“…Consequently, the results of this study, showing a significant improvement in self-efficacy during rehabilitation, are rather remarkable. Only a few other studies have assessed perceptions of personal control in patients with COPD [15,[52][53][54][55] and, therefore, this study contributes to the existing literature.…”
Section: Personal Controlmentioning
confidence: 89%
“…En estudios desarrollados con pacientes de EPOC se ha encontrado que la sensación de control y autoefi cacia ha sido relacionada como una forma de mejorar la adaptación (Taylor, 2007). En otros estudios se ha hallado que aquellos pacientes de EPOC con altas expectativas de autoefi cacia sobrevivieron por más tiempo que aquellos sin esas expectativas, estos resultados sugieren fuertemente que cuando una enfermedad es percibida como modifi cable y bajo el control personal, el proceso de recuperación de las enfermedades crónicas es más favorable en el tiempo (Kohler, Fish, & Greene, 2002). En defi nitiva, las creencias de control pueden llevar a individuos enfermos a poner en práctica conductas más saludables, a conseguir niveles más altos de adherencia al tratamiento y en alcanzar una mejor calidad de vida (Beneit & Latorre, 1994;Marks et al, 2008).…”
Section: Discussionunclassified
“…For Latinas awaiting GCRA who will be presented with a variety of risk-reducing strategies, a sense of confidence in being able to execute the recommendations is pertinent. High self-efficacy has been linked to numerous positive outcomes, such as breast self-examination (BSE) self-efficacy beliefs and higher levels of BSE adherence [36][37][38][39][40][41]. A few ethnic minority studies have also identified self-efficacy as playing an important role in healthy risk-reducing behaviors [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%